Laser-induced ultrafast spin current pulses: a thermodynamic approach. (24th April 2017) - Fognini, A; Michlmayr, T U; Vaterlaus, A; Acremann, Y
Abstract: The ultrafast demagnetization process allows for the generation of femtosecond spin current pulses. Here, we present a thermodynamic model of the spin current generation process, based on the chemical potential gradients as the driving force for the spin current. We demonstrate that the laser-induced spin current can be estimated by an easy to understand diffusion model.